(untitled) (Baghdad Science Journal, 2012)
Elevated C-Reactive Protein (CRP) level in serum is a risk factor for type 2 diabetes ,this relationship is likely to be the cause it means elevated CRP leads to T2D in future . Our objective was to examine CRP in male Type 2 Diabetes(T2D) patients in different age ,we studied 120 male subjects divided to two groups according to their age. First group A age (31 - 40) year old ,60 person )30 control & 30 T2D patients(,3 person for each same age: second group B age (41 – 50) years old ,60 person )30 control & 30 T2D patients(,3 person for each same age. We examined blood sugar ,cholesterol and CRP in each group. and we toke the mean of samples in the same age in each data in all the 4 groups. Our data shows that CRP raised significantly P?0.05 in group A(T2D) and in group B(T2D) comparing with control group of each .And cholesterol levels, and sugar levels raised significantly P?0.05 in group A(T2D) and in group B(T2D) comparing with control group of each. CRP ,Cholesterol and sugar are higher in group B(T2D) than in group A(T2D),and in group B (control) than in group A (control). CRP level can predict diabetes but not causal, diabetes may cause a kind of inflammation (showed by high CRP) by its effect on body and this effect (inflammation) may cause rising CRP level.